Four new suomilides isolated from the cyanobacterium Nostoc sp. KVJ20 and proposal of their biosynthetic origin - Schneider, Yannik K.-H.; Liaimer, Anton; Isaksson, Johan; Wilhelmsen, Oda S. B.; Andersen, Jeanette H.; Hansen, Kine Ø.; Hansen, Espen H. (Frontiers in Microbiology, 2023)
The suomilide and the banyasides are highly modified and functionalized non-ribosomal peptides produced by cyanobacteria of the order Nostocales. These compound classes share several substructures, including a complex azabicyclononane core, which was previously assumed to be derived from the amino acid tyrosine. In our study we were able to isolate and determine the structures of four suomilides, named suomilide B – E (1–4). The compounds differ from the previously isolated suomilide A by the functionalization of the glycosyl group. Compounds 1–4 were assayed for anti-proliferative, anti-biofilm and anti-bacterial activities, but no significant activity was detected. The sequenced genome of the producer organism Nostoc sp. KVJ20 enabled us to propose a biosynthetic gene cluster for suomilides. Our findings indicated that the azabicyclononane core of the suomilides is derived from prephenate and is most likely incorporated by a proline specific non-ribosomal peptide synthetase-unit.